Work Flow Redesign: The Key to Success When Using PACS - Siegel, Eliot L. (Springer-Verlag, 2003)

(untitled)
OBJECTIVE. Our objective is to emphasize the importance of work flow redesign, rather than filmless operation itself, to achieve cost reduction and improvement in productivity with picture archiving and communication systems (PACS). CONCLUSION. Our 8-year experience with PACS shows that the greatest benefit of the transition to a digital system has been the ability to use it as a tool to reengineer overall work flow, both in the imaging department and throughout the health care enterprise.